Health, employment and relationships: Correlates of personal wellbeing in young adults with and without a history of childhood language impairment. (July 2016) - Conti-Ramsden, Gina; Durkin, Kevin; Mok, Pearl L.H.; Toseeb, Umar; Botting, Nicola
Abstract: Objective: We examine the potential associations between self-rated health, employment situation, relationship status and personal wellbeing in young adults with and without a history of language impairment (LI). Methods: In total, 172 24-year-olds from the UK participated, with approximately half ( N = 84) having a history of LI. Personal wellbeing was measured using ratings from three questions from the Office for National Statistics regarding life satisfaction, happiness and life being worthwhile. Results: There were similarities between individuals with a history of LI and their age-matched peers in self-rated personal wellbeing. However, regression analyses revealed self-rated health was the most consistent predictor of personal wellbeing for individuals with a history of LI in relation to life satisfaction (21% of variance), happiness (11%) and perceptions that things one does in life are worthwhile (32%). None of the regression analyses were significant for their peers. Conclusions: Similarities on ratings of wellbeing by young adults with and without a history of LI can mask heterogeneity and important differences. Young adults with a history of LI are more vulnerable to the effects of health, employment and relationship status on their wellbeing than their peers. Highlights: Language impairment (LI) is a childhood disorder that can persist into adulthood. Average ratings of personal wellbeing of young adults with LI are similar to peers. Understanding factors that affect personal wellbeing in young adults is important. The wellbeing of young adults with LI is more vulnerable. Vulnerability is related to health, employment and relationship status factors.